Linux iinstallation and administration (Cambridge Course Technology, 2000)
Linux Operations and Administration introduces readers to Linux operations and system administration through a unified installation, using virtual machines. This text is more effective than those that take a professional approach because it eliminates confusion from working with differing hardware configurations, while allowing users to test interoperability between Linux and Windows. Detailed, yet reader-friendly, Linux Operations and Administration makes it easy to learn Linux and practice it with helpful in-text features like learning objectives and key terms, as well as items for self assessment such as review questions, hands-on activities, and case projects. - Publisher.
Contents note continued: Performance Tuning a Disk -- Fine-Tuning a File System -- Problem Solving in Linux -- Preventive Measures -- Recovering from a Disaster -- Troubleshooting Linux -- Using GRUB -- Login Problems -- Activity 20-4 Changing a Root Password -- File System Problems -- Network Troubleshooting -- Activity 20-5 Using the ping and traceroute Commands -- Chapter Summary -- Key Terms -- Review Questions -- Case Projects.
Includes index.
Keywords: Linux; Linux; Operating systems (Computers); Operating systems (Computers)